Extraction and modeling of lavender flower essential oil using supercritical carbon dioxide - Akgün, M; Akgün, NA; Dinçer, S (AMER CHEMICAL SOC, 2000)
Essential oil was extracted from lavender flowers (Lavandula Stoechas subspecies Cariensis Boiss) in a semicontinuous system by supercritical CO2. Experiments were carried out in the ranges of 8-14 MPa pressures, 308-323 K temperatures, and 1.092-2.184 x 10(-3) kg/min carbon dioxide now rates. The extraction process was modeled by a quasi-steady-state model as a function of extraction time, flow rate, pressure, and temperature. The model contains only one adjustable parameter, the intraparticle diffusion coefficient (effective diffusivity) D-e. The model using the best fit of D-e correlates the data satisfactorily.
Keywords: FLUID EXTRACTION; FRACTIONATION; COEFFICIENTS; MATRICES; SEED; Engineering